2021
DOI: 10.1093/nar/gkab448
|View full text |Cite
|
Sign up to set email alerts
|

The conserved sex regulator DMRT1 recruits SOX9 in sexual cell fate reprogramming

Abstract: Mammalian sexual development commences when fetal bipotential progenitor cells adopt male Sertoli (in XY) or female granulosa (in XX) gonadal cell fates. Differentiation of these cells involves extensive divergence in chromatin state and gene expression, reflecting distinct roles in sexual differentiation and gametogenesis. Surprisingly, differentiated gonadal cell fates require active maintenance through postnatal life to prevent sexual transdifferentiation and female cell fate can be reprogrammed by ectopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 66 publications
5
38
0
Order By: Relevance
“…This study establishes Lrh1 as a key regulator of testis development and function, performing essential functions both in somatic and germ line cells of the testis. We recently identified sex-biased differentially accessible regions (DARs) in Sertoli and granulosa cells that are likely to mediate sex-biased gene expression, and we found that these regions are enriched for the DNA motif bound by SF1 and LRH1 [63]. Because LRH1 had no reported function in the testis, we suggested that these sites might be bound by SF1.…”
Section: Plos Geneticsmentioning
confidence: 88%
See 1 more Smart Citation
“…This study establishes Lrh1 as a key regulator of testis development and function, performing essential functions both in somatic and germ line cells of the testis. We recently identified sex-biased differentially accessible regions (DARs) in Sertoli and granulosa cells that are likely to mediate sex-biased gene expression, and we found that these regions are enriched for the DNA motif bound by SF1 and LRH1 [63]. Because LRH1 had no reported function in the testis, we suggested that these sites might be bound by SF1.…”
Section: Plos Geneticsmentioning
confidence: 88%
“…We therefore examined published mRNA sequencing data, comparing expression of Lrh1 to that of Sf1 and key cell type-specific markers. In transcriptome data from purified populations of fetal pre-Sertoli and postnatal Sertoli cells, Lrh1 mRNA was not detectable between E11.5 and E13.5 [38], but it was present at low levels relative to Sf1 in juvenile Sertoli cells at P5, P7 and P10 [39,40] and then it was very low or absent in P18 and adult Sertoli cells [39]. In fetal and adult Leydig cells (E14.5, E18.5, P10, P21, P56), Sf1 mRNA was abundant as expected but, counter to some previous reports, Lrh1 expression was not detected in Leydig cells at any stage [41].…”
Section: Lrh1 Is Expressed In Juvenile Sertoli Cells and In Putative ...mentioning
confidence: 89%
“…In contrast, other results suggest that DMRT1 might regulate Sox9 expression as DMRT1 binds near the Sox9 locus in P28 mouse testes [ 81 ]. In any case, we currently know that the three transcription factors cooperate in the maintenance of the Sertoli cell fate, as Sertoli-to-granulosa transdifferentiation in the postnatal testis is faster and more efficient when Dmrt1 , Sox9 , and Sox8 are deleted in Sertoli cells, compared to single deletion of either Dmrt1 or Sox8/9 alone [ 84 , 97 ]. A recent study identified genes with Sertoli- and granulosa-biased postnatal expression and showed that many of them were associated with sex-biased differentially-accessible chromatin regions (DARs).…”
Section: Antagonism Between Male and Female Factors In Sexual Cell Fate Maintenancementioning
confidence: 99%
“…In postnatal Sertoli cells, many of the Sertoli-biased DARs were bound by both DMRT1 and SOX9, confirming again postnatal cooperation between the two transcription factors in maintaining the Sertoli cell fate. Furthermore, ChIP-seq analysis of granulosa cells ectopically expressing Dmrt1 or Sox9 indicated that DMRT1 and SOX9 jointly bind many sites, although SOX9 was unable to bind most of these sites in the absence of DMRT1, suggesting that during the transdifferentiation process, DMRT1 acts as a pioneer factor promoting chromatin accessibility at regions where SOX9 binds subsequently [ 97 ]. Nevertheless, the fact that ectopic SOX9 expression can reprogram sex-biased gene expression in vitro without activating Dmrt1 indicates that DMRT1-independent actions of SOX9 also exist during the Sertoli-to-granulosa transdifferentiation process [ 97 ].…”
Section: Antagonism Between Male and Female Factors In Sexual Cell Fate Maintenancementioning
confidence: 99%
See 1 more Smart Citation